Realokasi Subsidi BBM untuk Investasi Energi Terbarukan di Indonesia: Analisa Social Accounting Matrix - Toha, Sidik Nur; Soetjipto, Widyono (Jurnal Kebijakan Ekonomi, 2025)
The challenge of energy transition is the high subsidy on fossil fuels and financing needs. Using social accounting matrix, this study examines the impact of energy transition plan and subsidy reform on economy, society and environment through three scenarios: business-as-usual scenario (Sim1), energy transition (Sim2) and phasing-out (Sim3). Sim2 and Sim3 are conducted without subsidy transfer (Sim2 & Sim3) and subsidy transfer for financing renewable power plants (Sim2.1 & Sim 3.1). The result is Sim3 has better economic, social and environmental impacts than Sim1. When reallocation is conducted, reallocation simulation shows positive impacts on economy and society with significant differences in environmental impacts.